Caffeine`s effect on intermittent sprint cycling performance with different rest intervals - Lee, C. L.; Cheng, C. F.; Lin, J. C.; Huang, H. W. (European Journal of Applied Physiology, 2012)
The purpose of this study was to investigate the effects of caffeine ingestion on the performance of an intermittent sprint cycling test (ISCT) with different rest intervals. Fourteen males with team sport experience consumed 6 mg kg-1 of caffeine or a placebo 60 min prior to completing two sets of an ISCT with 4-min rest intervals. Each set consisted of 12 × 4-s sprints with 20- or 90-s active recovery intervals at 60-70 rpm. Blood lactate was collected at baseline and immediately following the completion of six sprints in each set. At 20-s recovery intervals, peak power and total work were not significantly different between conditions during the ISCT (P > 0.05); but caffeine reduced 6.31% effort for mean power in Sprint 10 of the later stage, as well as an increased fatigue index and elevated blood lactate levels during the ISCT (P < 0.05). At 90-s recovery intervals, peak power, mean power, and total work under caffeine conditions were significantly higher than under placebo conditions during the ISCT (P < 0.05), but no differences were apparent in fatigue index and blood lactate levels (P > 0.05). In conclusion, caffeine ingestion may be ergolytic, affecting performance and fatigue development in the later stage during a prolonged and intermittent sprint test with a short recovery interval. However, caffeine produces an ergogenic effect in the initial stage of an intermittent sprint performance with a longer recovery interval.